2014
DOI: 10.1038/cddis.2014.159
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of glycated chitosan with high-intensity focused ultrasound on suppression of metastases in a syngeneic breast tumor model

Abstract: Stimulation of the host immune system is crucial in cancer treatment. In particular, nonspecific immunotherapies, when combined with other traditional therapies such as radiation and chemotherapy, may induce immunity against primary and metastatic tumors. In this study, we demonstrate that a novel, non-toxic immunoadjuvant, glycated chitosan (GC), decreases the motility and invasion of mammalian breast cancer cells in vitro and in vivo. Lung metastatic ratios were reduced in 4T1 tumor-bearing mice when intratu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Interestingly, ultrasound exposure to cultured PC3 prostate cancer cells incubated with microbubbles have demonstrated reduced cell migration and invasion with reduced MMP-2 and MMP-9 expression (35). In another study, metastasis was reduced in mice bearing breast 4T1 tumors when mice were injected with microbubbles and had tumors sonicated (36). These results as well as our own suggest that tumor sonication with ultrasound contrast agents is more likely to inhibit rather than promote tumor metastasis.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, ultrasound exposure to cultured PC3 prostate cancer cells incubated with microbubbles have demonstrated reduced cell migration and invasion with reduced MMP-2 and MMP-9 expression (35). In another study, metastasis was reduced in mice bearing breast 4T1 tumors when mice were injected with microbubbles and had tumors sonicated (36). These results as well as our own suggest that tumor sonication with ultrasound contrast agents is more likely to inhibit rather than promote tumor metastasis.…”
Section: Discussionsupporting
confidence: 56%
“…13D & E, respectively) did not enhance the antimigratory activity of ranibizumab opposing the enhanced anti-angiogenic effect obtained in the capillary-like tubule formation assay (Section 3.7.2.2). The anti-migratory activity of chitosan is not yet fully understood, with studies reporting both pro-and inhibitory effects on cell migration (23,108,109) . However, the difference in the anti-angiogenic activity between the two assays may be due to two reasons.…”
Section: (B)mentioning
confidence: 99%
“…In the treatment of line 1 lung adenocarcinoma in mice, a poorly immunogenic tumor model, a 1.67% GC solution enabled a noncurative mesosubstituted tetra (meta-hydroxy-phenyl) chlorin–based PDT (mTHPC-PDT) to cure 37% of the tumor-bearing mice [67]. In the treatment of 4T1 mammary sarcoma in mice, another poorly immunogenic tumor model, 1% GC solution decreased the sizes of tumor metastases when combined with high-intensity focused ultrasound (HIFU) treatment (instead of photothermal application), and the serum from treated mice showed significant cytotoxic effects on 4T1 cells [69]. These results confirmed our previous studies, showing that GC is a critical component in the application of inCVAX for the treatment of metastatic cancer.…”
Section: Effects Of Incvaxmentioning
confidence: 99%
“…With the direct immunostimulation properties, GC could stimulate macrophage activation, as measured by TNF-α secretion and NO production [ 8 5], and enhance CD80 expression that indicates the DCs maturation [ 2 2]. Studies on the direct interaction with tumor cells showed that GC has no cytotoxicity on tumor cells, but could decrease the expression of Twist-1 and Slug, proto-oncogenes commonly implicated in metastasis [69]. When GC alone is used as a treatment agent on tumor bearing mice, the metastases can be decreased, and survival time can be extended; however, the survival rate of animals has not been improved [21–22,69], demonstrating the adjuvant nature of GC.…”
Section: Mechanism Of Incvaxmentioning
confidence: 99%